Sesame as an Alternative Host Plant to Establish and Retain Predatory Mirids in Open-Field Tomatoes - Castillo, Jose; Roda, Amy; Qureshi, Jawwad A.; Pérez-Hedo, Mertixell; Urbaneja, Alberto; Stansly, Philip A. (MDPI, 2022)
The silverleaf whitefly (Bemisia tabaci) and the South America tomato pinworm (Tuta absoluta) are two of the most destructive pests of tomato. Open-field tomato production frequently relies on chemical treatments, which has been shown to lead to pesticide resistance. The integration of biological control using predatory mirid bugs is an effective alternative method for managing these pests. However, methods to establish and maintain populations of zoophytophagous mirids are not adequately described. We explored the potential use of two mirids naturally occurring in Florida, Nesidiocoris tenuis and Macrolophus praeclarus. We conducted 6 field experiments over 4 consecutive years to develop a strategy to maintain the mirids. Pre-plant inoculation of tomato plants did not lead to their establishment, likely due to the low prevalence of prey. We explored the use of sesame (Sesamum indicum) to retain the mirids. Intercropping sesame maintained the populations of N. tenuis throughout the duration of the crop. Macrolophus praeclarus never established in any of the open-field experiments. Nesidiocoris tenuis damage was minimal (<1 necrotic ring/plant) and mirid damage was reduced in the presence of sesame. Our results show that intercropping sesame may provide a means to utilize mirids to manage B. tabaci, an established pest, and provide options to tomato growers should T. absoluta invade USA.